Search for time-dependent 𝐶⁢𝑃 violation in 𝐷0→𝜋+⁢𝜋−⁢𝜋0 decays - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Celani, Sara; Cocha Toapaxi, Carlos; De Cian, Michel; Dittmann, Lucas; Glaser, Fabian; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Herrero Gascón, Paula; et al. (Physical review letters, 2024)
A measurement of time-dependent 𝐶⁢𝑃 violation in 𝐷0→𝜋+⁢𝜋−⁢𝜋0 decays using a 𝑝⁢𝑝 collision data sample collected by the LHCb experiment in 2012 and from 2015 to 2018, corresponding to an integrated luminosity of 7.7 fb−1, is presented. The initial flavor of each 𝐷0 candidate is determined from the charge of the pion produced in the 𝐷*⁢(2010)+→𝐷0⁢𝜋+ decay. The decay 𝐷0→𝐾−⁢𝜋+⁢𝜋0 is used as a control channel to validate the measurement procedure. The gradient of the time-dependent 𝐶⁢𝑃 asymmetry Δ⁢𝑌 in 𝐷0 →𝜋+⁢𝜋−⁢𝜋0 decays is measured to be Δ⁢𝑌=(−1.3±6.3±2.4)×10−4, where the first uncertainty is statistical and the second is systematic, which is compatible with 𝐶⁢𝑃 conservation.
The LHCb collaboration: R. Aaij, S. Bachmann, L. Carus, R. Caspary, S. Celani, C. Cocha Toapaxi, M. De Cian, L. Dittmann, F.C. Glaser, P.A. Günther, X. Han, S. Hansmann-Menzemer, P. Herrero Gascon, J. Hu, C. Langenbruch, B. Leverington, J. Marks, M.P. Morgenthaler, S.R. Roy, M. Ruiz Diaz, G. Tuci, L.H. Uecker, D.J. Unverzagt, U. Uwer, C. Wang, L. Witola, Y. Zhao, A. Zhelezov [und zahlreiche weitere]
Gesehen am 14.10.2026